Synthesis of IWMI work in Nepal - Pant, Dhruba; Samad, Madar (International Water Management Institute, 2010)
The International Water Management Institute (IWMI) has been working in Nepal since 1986 with the objective of undertaking research in water management and to strengthen the research capabilities of concerned government agencies. The research helped to develop appropriate mechanisms for providing support to Farmer-Managed Irrigation Systems (FMIS) and the initiation of participatory irrigation management (PIM). The river basin studies helped policy formulation for integrated planning and management of water resources besides the methodological contribution through the development of appropriate tools for water management studies. It also contributed to enhancing the capabilities of agency officials and local researchers through their involvement in research activities.